Optical diagnostic imaging and therapy for thyroid cancer. (15th December 2022) - Shao, Chengying; Li, Zhenfang; Zhang, Chengchi; Zhang, Wanchen; He, Ru; Xu, Jiajie; Cai, Yu
Abstract: Thyroid cancer, as one of the most common endocrine cancers, has seen a surge in incidence in recent years. This is most likely due to the lack of specificity and accuracy of its traditional diagnostic modalities, leading to the overdiagnosis of thyroid nodules. Although there are several treatment options available, they are limited to surgery and 131 I radiation therapy that come with significant side effects and hence cannot meet the treatment needs of anaplastic thyroid carcinoma with very high malignancy. Optical imaging that utilizes optical absorption, refraction and scattering properties, not only observes the structure and function of cells, tissues, organs, or even the whole organism to assist in diagnosis, but can also be used to perform optical therapy to achieve targeted non-invasive and precise treatment of thyroid cancer. These applications of screening, diagnosis, and treatment, lend to optical imaging's promising potential within the realm of thyroid cancer surgical navigation. Over the past decade, research on optical imaging in the diagnosis and treatment of thyroid cancer has been growing year by year, but no comprehensive review on this topic has been published. Here, we review key advances in the application of optical imaging in the diagnosis and treatment of thyroid cancer and discuss the challenges and potential for clinical translation of this technology. Graphical abstract: Image 1